Estudio del impacto social y económico en trabajadores agrícolas colombianos generado por comercio justo (2020)
The Colombian agricultural population has not increased significantly compared to the last 50 years, with the total population of the country has increased significantly. This means that agricultural demand has grown meaningfully. However, demand has been covered through imports and unmeasured and poorly planned land occupation. Despite the existence of projects that seek to support peasants, their standard of living is unsatisfactory. Terra Eterna is a company that encourages agricultural work through good treatment and recognition towards the worker. Nevertheless, this company is unaware of whether it is causing any impact on the peasant community with which it works. Through the Viable System Model, the company was structured as a system, and an internal information system was implemented. It will provide knowledge to the company with real and necessary data, and identify whether its social purpose is being fulfilled. The proposed model was explained and developed so that the companies concerned can replicate it.